Technical approaches to single port/incision laparoscopic appendicectomy: a literature review - Rehman, H (The Royal College of Surgeons of England, 2011)
INTRODUCTION: Single port/incision laparoscopic surgery (SPILS) is a modern advancement toward stealth surgery. Despite the paucity of high-quality scientific studies assessing its effectiveness, this procedure is being used increasingly. This review aims to describe commonly used techniques for SPILS appendicectomies (SPILA), to summarise complication rates in the literature and to provide discussion on indications and implementation. METHODS: All available databases including the Cochrane Central Register of Controlled Trials, MEDLINE® and Embase™ were searched in February 2011 and cross-referenced for available English literature describing SPILA in patients of any age. RESULTS: Three broad technical approaches are described: procedures using laparoscopic instruments through a single skin incision in the abdominal wall, regardless of the number of fascial incisions, with or without the additional use of percutaneous sutures or wires to ‘assist’ the operation, and hybrid procedures, in which the appendix is exteriorised using a single incision laparoscopically assisted operation but subsequently divided using a conventional ‘open’ appendicectomy technique. Complication rates seem to be highest in SPILA procedures unassisted by sutures or wires. CONCLUSIONS: Future research assessing the efficacy of single incision laparoscopic procedures should consider variation in technique as a possible factor affecting outcome.